Palaeopermeability anisotropy and geometrical properties of sealed-microfractures from micro-CT analyses: An open-source implementation. (February 2019) - Gomila, Rodrigo; Arancibia, Gloria; Mery, Domingo; Nehler, Mathias; Bracke, Rolf; Morata, Diego
Highlights: We present a 4-step procedure, from field sampling to permeability modelling. Spatial orientation of the sample is kept from the physical to the virtual world. Geometric parameters of fault-related microfracture network are measured. Palaeopermeability anisotropy of a fault-related microfracture network is modelled. Abstract: Fault zone permeability and the real 3D-spatial distribution of the fault-related fracture networks are critical in the assessment of fault zones behavior for fluids. The study of the real 3D-spatial distribution of the microfracture network, using X-ray micro-computed tomography, is a crucial factor to unravel the real structural permeability conditions of a fault-zone. Despite the availability of several commercial software for rock properties estimation from X-ray micro-computed tomography scanning, their high cost and lack of programmability encourage the use of open-source data treatment. This work presents the implementation of a methodology flow for the quantification of both structural and geometrical parameters (fractures density, fractures aperture, fractures porosity, and fractures surface area), and the modeling of palaeopermeability of fault-related fractured samples, with focus in the proper spatial orientation of both the sample and the results. This is performed with an easy to follow step-by-step implementation, by a combination of open-source software, newly implemented codes, and numerical methods. This approach keeps track of the sample's spatial orientation from the physical to the virtual world, thus assessing any fault-related palaeopermeability anisotropy.